Multiligament knee injuries with associated tibial plateau fractures: A report of two cases - Sabesan, Vani J (World J Orthop, 2015)
The management of a combination of fracture and multiligament knee injury (MKI) in traumatic knee injury remains controversial, and there are evolving treatment recommendations. Currently, there are no studies focusing on older adult patients with MKI’s in combination with tibia fractures. As a result, there is no well-established treatment algorithm for older adult patients with these complex injuries. We report two cases of MKI’s with concomitant fractures in patients fifty years of age or older. Both patients were treated surgically for their associated tibial plateau fractures, but were managed with conservative treatment of the multiligamentous knee injuries. We also provide a review of the literature and guidelines for older adult patients with these types of complex traumatic injuries. Early to mid term acceptable outcomes were achieved for both patients through surgical fixation of the tibial plateau fracture and conservative treatment of the ligament injuries. We propose a comprehensive treatment algorithm for management of these complex injuries.